Recent Advances in Photoacoustic Agents for Theranostic Applications - Seongyi Han; Tsedendamba Ninjbadgar; Mijeong Kang; Chulhong Kim; Jeesu Kim (Nanomaterials, 2023)
Photoacoustic agents are widely used in various theranostic applications. By evaluating the biodistribution obtained from photoacoustic images, the effectiveness of theranostic agents in terms of their delivery efficiency and treatment responses can be analyzed. Through this study, we evaluate and summarize the recent advances in photoacoustic-guided phototherapy, particularly in photothermal and photodynamic therapy. This overview can guide the future directions for theranostic development. Because of the recent applications of photoacoustic imaging in clinical trials, theranostic agents with photoacoustic monitoring have the potential to be translated into the clinical world.